Farmers Perception on Effect of Pesticide on Insect Pollinators at Padampur and Jutpani Vdcs, Chitwan, Nepal - Pudasaini, R.; Thapa, R. B.; Tiwari, S. (International Journal of Applied Sciences and Biotechnology, 2016)
A survey was conducted to know the farmers perception on the effect of chemical pesticide on insect pollinators at Jutpani andPadampur VDCs, Chitwan, Nepal in 2013. Thirty households were randomly selected and semi-structured questionnaire was used to collect necessary information by face-to-face interview. Majority of the farmers (60%)applied pesticides on crops during mid day. Half of the farmers (50.00%) rankedpopulation decline as effect of pesticide on pollinators, some farmers (16.67%) also observed dead pollinators in field and hives, affecting their distribution (13.33%) and repelling them from field as mentioned by the respondents (13.33%). Majority of respondents (56.67%) perceived that misuse and overuse of chemical pesticide was the major cause of declining insect pollinators, among other causes, 16.67% farmers replied deforestation, 10.00% environmental pollution and 6.67% less cultivated area responsible for the decline. Very few farmers (6.67%) could realise the incidence of disease on pollinator due to pesticidal effects. Int J Appl Sci Biotechnol, Vol 4(1): 64-66